Implementable Mechanisms to Coordinate Horizontal Alliances - Nault, Barrie R.; Tyagi, Rajeev K. (Management Science, 2001)
Unprecedented changes in the economics of interaction, mainly as a result of advances in information and telecommunication technologies such as the Internet, are causing a shift toward more networked forms of organizations such as horizontal alliances—that is, alliances among firms in similar businesses that have positive externalities between them. Because the success of such horizontal alliances depends crucially on aligning individual alliance-member incentives with those of the alliance as a whole, it is important to find coordination mechanisms that achieve this alignment and are simple-to-implement. In this paper, we examine two simple coordination mechanisms for a horizontal alliance characterized by the following features: (i) firms in the alliance can exert effort only in their “local” markets to increase customer demand for the alliance; (ii) customers are mobile and a customer living in a given alliance member's local area may have a need to buy from some other alliance member; and (iii) the coordination rules followed by the alliance determine which firms from a large pool of potential member-firms join the alliance, and how much effort each firm joining the alliance exerts in its local market. In this horizontal alliance setup, we consider the use of two coordination mechanisms: (i) a linear transfer of fees between members if demand from one member's local customer is served by another member, and (ii) ownership of an equal share of the alliance profits generated from a royalty on each member's sales. We derive conditions on the distribution of demand externalities among alliance members to determine when each coordination mechanism should be used separately, and when the mechanisms should be used together.